Optimizing Personal Data Protection in Indonesia: Lesson Learned from China, South Korea, and Singapore - Diana Setiawati; Hary Abdul Hakim; Fahmi Adam Hasby Yoga (Indonesian Comparative Law Review, 2020)
Industrial revolution 4.0 offers both opportunities and challenges to all countries, including Indonesia. Personal data protection is necessary to encourage digital innovation. The existing regulation relating to personal data in Indonesia does not give sufficient protection especially with regard to the use of artificial intelligence and therefore is inadequate to encourage digital economic development. This paper aims to explore the importance of strong data protection regulation in Indonesia. This normative legal research employs comparative approach. Comparative study was made upon the development of personal data protection regulation in China, South Korea and Singapore. The study shows that these countries provide good lesson for Indonesia to learn in developing personal data protection regulation.